Non-commercial fish catches with experimental bottom long line fishing in Gorgona Island, Colombia, and its surroundings areas - Gómez, Stella; Caicedo, Julián Alejandro; Zapata, Luis Alonso (Revista de Biología Tropical, 2014)
Eels and moray eels are among the species that lack commercial value but that are important as bait. However, little information is available about Colombian fishing by-products. Between 2005 and 2009, field work was done in Gorgona National Natural Park and its surrounding areas, with a fishing line made of traditional “J” and circular or curve hooks. We analyzed the catch composition, comparing both types of hooks, emphasizing whether the circular hook modified or not non-commercial captures. Overall, 189 fishing throws where analyzed, standardizing the Catch Per Effort (CPUE) in number of individuals and in kilograms per 100 hooks per hour of task. A total of 50 species where captured, of which 14 are part of the non-commercial category. There were no significant differences for hook types (U=25228, P>0.1), and Gymnothorax equatorialis and Echiophis brunneus were the most abundant species. Both were concentrated in the northern sector of the study area, a rocky banks sector. The mean sexual maturity size was 57.0cm in G. equatorialis, and at 85.6cm in E. brunneus. Rev. Biol. Trop. 62 (Suppl. 1): 391-405. Epub 2014 February 01.